Investigation of Contributing Factors to Road Traffic Accidents in Thailand by Using Latent Class Analysis - Laochareonsuk, Tarn; Runganothai, Sahassawat; Piantanakulchai, Mongkut (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 28, 2023)